Nonfunctional requirements in systems analysis and design - Adams, Kevin MacG (Topics in Safety, Risk, Reliability and Quality, 2015)
This book will help readers gain a solid understanding of non-functional requirements inherent in systems design endeavors. It contains essential information for those who design, use, and maintain complex engineered systems, including experienced designers, teachers of design, system stakeholders, and practicing engineers. Coverage approaches non-functional requirements in a novel way by presenting a framework of four systems concerns into which the 27 major non-functional requirements fall: sustainment, design, adaptation, and viability. Within this model, the text proceeds to define each non-functional requirement, to specify how each is treated as an element of the system design process, and to develop an associated metric for their evaluation. Systems are designed to meet specific functional needs. Because non-functional requirements are not directly related to tasks that satisfy these proposed needs, designers and stakeholders often fail to recognize the importance of such attributes as availability, survivability, and robustness. This book gives readers the tools and knowledge they need to both recognize the importance of these non-functional requirements and incorporate them in the design process.